The guardian - Flynn, Beau.; Vinson, Tripp; Brinkerhoff, Ron L.; Davis, Andrew, 1946-; Costner, Kevin; Kutcher, Ashton, 1978-; Ward, Sela.; Sagemiller, Melissa; Brown, Clancy; Hardwick, Omari; Daniels, Alex.; Pea, Adam.; et al. (Burbank, CA : Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
Ben Randall's (Costner) Coast Guard rescue team is killed in a horrific rescue mission following the breakup of his marriage, which leaves him an emotional wreck. He's forced to take over an 18-week grueling basic training course where he meets a hot-shot recruit whose bravado is tested. Links are made between the two men that make them appear to be psychic twins.
Originally released as a motion picture in 2006.
Special features: Never-before-seen alternate ending with on-camera introduction by Andrew Davis; deleted scenes with optional commentary by director Andrew Davis and writer Ron L. Brinkerhoff; "Unsung heroes": a tribute to the real-life U.S. Coast Guard Rescue Swimmers; "Making waves": the making-of 'The guardian'; audio commentary with director Andrew Davis and writer Ron L. Brinkerhoff.
Director of photography, Stephen St. John ; edited by Thomas J. Nordberg, Dennis Virkler ; music by Trevor Rabin ; costume designer, Mark Peterson ; production designer, Maher Ahmad ; art directors, Andrew M. Cahn and Austin Gorg ; visual effects producer, Susan Zwerman.
MPAA rating: PG-13; for intense sequences of action/peril, brief strong language and some sensuality.
Rated: PG-13.
DVD, dual-layer format, region 1; Dolby Digital 5.1 surround.
Keywords: United States. -- Coast Guard -- Drama; Rescue work -- Drama; Survival swimming -- Drama; Drowning -- Prevention -- Drama; Lifesaving -- Drama; Feature films; Thrillers (Motion pictures); DVDs for the hearing impaired; Action and adventure films